Prima e dopo il «sorbetto di Leopardi». Savinio e «Il Mediterraneo» tra cronaca e letteratura - Sgroi, Alfredo (Italogramma, 2020)
<span dir="ltr" style="left: calc(var(–scale-factor)*85.10px); top: calc(var(–scale-factor)*171.88px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.929552);" role="presentation">Many parts of Savinio's work are still unknown. In this essay an unknown aspect of his <span dir="ltr" style="left: calc(var(–scale-factor)*85.10px); top: calc(var(–scale-factor)*185.68px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.983194);" role="presentation">activity is analyzed: the collaboration with the periodical <span dir="ltr" style="left: calc(var(–scale-factor)*380.11px); top: calc(var(–scale-factor)*185.68px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.985305);" role="presentation">«Il Mediterraneo». In this <span dir="ltr" style="left: calc(var(–scale-factor)*85.10px); top: calc(var(–scale-factor)*199.48px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.944063);" role="presentation">newspaper Savinio published many articles between 1939 and 1941. In them we find <span dir="ltr" style="left: calc(var(–scale-factor)*85.10px); top: calc(var(–scale-factor)*213.28px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.903165);" role="presentation">new themes, many philosophical arguments, hypotheses of later narrative works.